PREDICTION OF MEANING OF LIFE IN STUDENT BASED ON SPIRITUALITY, SELF-ESTEEM, AND POSITIVE AFFECT - Sab, Leila; Ghomian, Sohila (Revista Inclusiones, 2019)
Introduction: The meaning of life is one of the important components of purposefulness, mental health, and psychological well-being. Having a meaning in life is effective in the development of a positive feeling towards yourself and the surrounding world as well as targeted direction. Considering the lack of a study related to this field in Iran, the purpose of current study is to predict the meaning of life based on the components of spirituality, self-esteem and positive affect in college students. Method: 462 male and female students of Shahed University were selected by proportional sampling method and answered the tools of current study, such as the LAP-R, SAI, SERS-SF and PANAS. Results: According to the results of current study, the three factors of spirituality, self-esteem and positive affect were able to predict the meaning of life in students. Conclusion: Based on these findings, the tendency toward spirituality, increasing self-esteem and positive affects can increase the meaning of life in student samples